Author Correction: Landscape of multi-nucleotide variants in 125,748 human exomes and 15,708 genomes (Nature Communications, (2020), 11, 1, (2539), 10.1038/s41467-019-12438-5) - Wang, Qingbo (Nature Research, 2022)
10.1038/s41467-021-21077-8